Targeting β-catenin: PROTACs and precision degraders for Wnt-driven cancers - Trapani, Jonathan; Caroland, Kailey P.; Ahmed, Yashi; Robbins, David J.; Weiss, Vivian L.; Lee, Ethan (Frontiers in Oncology, 2026)
The Wnt signaling pathway, a highly conserved molecular cascade, orchestrates critical biological processes including embryonic development, cell differentiation, and proliferation across diverse organisms. Despite the pivotal role that Wnt signaling plays in many diseases, most notably cancer, there are still no FDA-approved, efficacious drugs available that inhibit this pathway. Most Wnt inhibitors target upstream components (e.g., Wnt ligand production and receptors) rather than the most commonly mutated downstream proteins in the pathway. Consequently, there is considerable interest in developing drugs that target the downstream effector, β-catenin. This review examines the challenges in targeting β-catenin, current approaches, and insights into overcoming on-target toxicity associated with cadherin-bound β-catenin.